A method for preparing nano calcium carbonate by using carbide mud, ammonium chloride and carbon dioxide
Patent Information
- Application Number
- CN202611285268.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-09
AI Technical Summary
如果二氧化碳局部浓度过高或传质不均匀,容易造成局部过碳化、非均匀成核以及晶型和粒径失控;若碳化不足,则可能存在游离钙残留
本发明以工业固体废弃物电石泥为钙源,以含二氧化碳气体为碳化碳源,通过氯化铵转化、杂质分离、含钙溶液净化和受控碳化,将电石泥中的有效钙组分转化为高附加值纳米碳酸钙,实现了工业固体废弃物电石泥由低附加值消纳利用向高值无机功能材料利用的转变,有利于提高电石泥资源化利用水平,并降低纳米碳酸钙生产对高纯石灰石等传统钙资源的依赖。
Smart Images

Figure CN122877791A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical technology, and in particular to a method for preparing nano-calcium carbonate using carbide sludge, ammonium chloride, and carbon dioxide. Background Technology
[0002] Calcium carbide sludge is a large-scale industrial solid waste generated during the calcium carbide process for acetylene production. Its main active ingredient is calcium hydroxide, but it also typically contains silicon, aluminum, iron, magnesium, carbon slag, and other insoluble impurities. Due to its high moisture content, fluctuating composition, and complex impurities, calcium carbide sludge presents significant challenges in storage, transportation, and disposal. Current utilization methods for calcium carbide sludge are mainly concentrated in cement, building materials, flue gas desulfurization, and soil improvement, but these are generally low-value-added uses with limited product value and resource utilization efficiency. Therefore, transforming the calcium resources in calcium carbide sludge from general disposal to high-value utilization is of great significance for improving the resource utilization level of industrial solid waste.
[0003] Nano-calcium carbonate, with its small particle size, large specific surface area, and excellent reinforcing, filling, and surface effects, is widely used in plastics, rubber, coatings, adhesives, and papermaking, among other fields. Its added value is significantly higher than that of ordinary calcium-containing building materials. Calcium carbide sludge contains a high proportion of calcium hydroxide, which theoretically can be used as a calcium source for calcium carbonate production. If the effective calcium components in calcium carbide sludge can be extracted, purified, and further processed into nano-calcium carbonate, the dependence on traditional calcium sources such as high-purity limestone for nano-calcium carbonate production can be reduced, realizing the transformation of industrial solid waste into high-value-added inorganic functional materials.
[0004] Meanwhile, the resource utilization of carbon dioxide and the conversion of carbon dioxide into stable carbonates through mineralization reactions are important technological approaches to carbon sequestration and carbon resource utilization. Calcium hydroxide in calcium carbide sludge is highly alkaline, and its calcium component can react with carbon dioxide to form calcium carbonate. Therefore, combining the resource utilization of calcium carbide sludge with carbonation reactions containing carbon dioxide gas can convert the effective calcium component in calcium carbide sludge into calcium carbonate, while simultaneously converting the carbon dioxide involved in the reaction into stable carbonate components in the product. This technological approach combines the utilization of industrial solid waste, the mineralization of carbon dioxide, and the production of high-value-added calcium carbonate.
[0005] However, when directly carbonizing calcium carbide sludge to prepare nano-calcium carbonate, silicon, aluminum, iron, magnesium, carbon slag, and other insoluble impurities and soluble metal ions can easily interfere with the nucleation and crystal growth of calcium carbonate, resulting in problems such as low purity, wide particle size distribution, unstable crystal form, and easy particle agglomeration, making it difficult to consistently obtain high-quality nano-calcium carbonate. Some existing processes use acid leaching or ammonium salt leaching to convert calcium in calcium carbide sludge into soluble calcium salts, but these processes may still have problems such as high acid consumption, equipment corrosion, ammonia release, difficulty in recycling ammonium and chlorine-containing mother liquor, large wastewater discharge, and insufficient control of the carbonization process.
[0006] Furthermore, the formation of nano-calcium carbonate depends not only on the purity of the calcium source but also on the mass transfer efficiency of carbon dioxide, carbonation temperature, gas concentration and flow rate, system alkalinity, stirring conditions, crystal form control agents, and the carbonation endpoint. If the local carbon dioxide concentration is too high or the mass transfer is uneven, it can easily lead to localized over-carbonization, non-uniform nucleation, and loss of control over crystal form and particle size; if carbonization is insufficient, free calcium residue may remain. Therefore, how to achieve concentrated and uniform nucleation of nano-calcium carbonate while improving carbon dioxide utilization efficiency is another key issue in the preparation of high-quality nano-calcium carbonate from calcium carbide sludge.
[0007] Therefore, it is necessary to provide a method for preparing nano-calcium carbonate using calcium carbide sludge, an industrial solid waste, as the calcium source and carbon dioxide gas as the carbon source. Through processes such as calcium carbide sludge pretreatment, ammonium chloride conversion, calcium-containing solution purification, alkaline carbonation, crystal form and particle size control, and mother liquor recycling, the method can realize the high-value utilization of calcium resources in calcium carbide sludge and the mineralization utilization of carbon dioxide, further improve the product quality and production stability of nano-calcium carbonate, and reduce the consumption of traditional calcium sources and fresh chemical raw materials and pollutant emissions. Summary of the Invention
[0008] In order to solve the problems existing in the prior art, the present invention provides a method for preparing nano-calcium carbonate using carbide sludge, ammonium chloride and carbon dioxide, so as to solve the current technical problems.
[0009] The technical solution adopted by this invention to solve its technical problem is: This invention provides a method for preparing nano-calcium carbonate using carbide sludge, ammonium chloride, and carbon dioxide, comprising the following steps: S1. The moisture content and calcium hydroxide content of the calcium carbide mud are determined. The calcium carbide mud is measured on a dry basis. The calcium carbide mud is mixed with water and then crushed, sieved or wet dispersed to obtain calcium carbide mud slurry. S2. The calcium carbide slurry is mixed with ammonium chloride solution, and a conversion reaction is carried out under the conditions that the molar ratio of ammonium chloride to effective calcium hydroxide in calcium carbide slurry is 1.80 to 2.40 and the reaction temperature is 25 to 80°C, so that calcium hydroxide is converted into soluble calcium chloride and ammonia is generated. Then, solid-liquid separation is carried out to remove insoluble impurities and obtain a calcium-containing solution containing calcium chloride. S3. The calcium-containing solution is purified, and the calcium ion concentration of the purified calcium-containing solution is adjusted to 0.20-1.50 mol / L; S4. Add ammonia water and / or introduce ammonia gas into the adjusted calcium-containing solution to make the system alkaline, and add a crystal form control agent to obtain the carbonization precursor solution. S5. Under the conditions of 5-45℃ and stirring, a gas containing carbon dioxide is introduced into the carbonation precursor liquid. By controlling the carbon dioxide volume concentration, the gas flow rate per unit volume of precursor liquid, the stirring intensity and the carbonation endpoint, calcium ions react with carbon dioxide to form calcium carbonate crystal nuclei and inhibit the continued growth of crystal grains, thus obtaining nano-calcium carbonate slurry. S6. The nano-calcium carbonate slurry is subjected to aging, solid-liquid separation, washing, drying and dispersion treatment in sequence to obtain nano-calcium carbonate.
[0010] Preferably, the calcium carbide sludge in step S1 is at least one of wet-discharged calcium carbide sludge, filter-pressed calcium carbide sludge, or dried calcium carbide sludge; the calcium carbide sludge has a calcium hydroxide mass fraction of 45% to 95% on a dry basis, and particles and foreign matter with a particle size greater than 1 mm are separated from the calcium carbide sludge slurry before the conversion reaction.
[0011] Preferably, in step S2, the mass fraction of the ammonium chloride solution is 8% to 30%, the molar ratio of ammonium chloride to effective calcium hydroxide is 1.95 to 2.20, and the temperature of the conversion reaction is 40 to 70°C and the time is 30 to 180 min.
[0012] Preferably, step S2 is carried out in a closed or slightly negative pressure reactor. The ammonia-containing gas discharged from the reactor is successively defoamed and condensed, and then absorbed by water, dilute ammonia water or purified calcium-containing solution. The resulting ammonia water or ammonia-containing calcium-containing solution is returned to step S4.
[0013] Preferably, the solid-liquid separation in step S2 includes sedimentation, centrifugation, plate and frame filtration, membrane filtration, or a combination thereof; the filtration accuracy of the solid-liquid separation is 0.5 to 100 μm, and the resulting filter residue is washed with water, with the washing liquid being incorporated into the calcium-containing solution.
[0014] Preferably, the purification in step S3 includes: adjusting the pH of the calcium-containing solution to 8.0-10.5 and keeping it at a temperature of 10-60 min, so that at least one impurity among iron, aluminum, and magnesium forms a precipitate or is adsorbed by insoluble particles; and then removing the impurities by at least one of a 1-20 μm precision filter and a 0.1-5 μm security filter.
[0015] Preferably, the suspended solids content in the purified calcium-containing solution in step S3 is not higher than 200 mg / L, and the calcium ion concentration is adjusted to 0.30–1.00 mol / L by diluting with water, evaporating and concentrating, or mixing with calcium-containing solutions of different concentrations.
[0016] Preferably, in step S4, the amount of ammonia water and / or ammonia gas added is calculated as free ammonia, the molar ratio of free ammonia to calcium ions is 1.80 to 2.40, and the initial pH of the carbonization precursor solution is adjusted to 10.5 to 12.5.
[0017] Preferably, the crystal form control agent is selected from one or more of citric acid, citrate, polyacrylic acid or its salts, hexametaphosphate, pyrophosphate, ethylenediaminetetraacetic acid or its salts, polyethylene glycol, sucrose, and soluble magnesium salts; based on the theoretical mass of calcium carbonate produced, the amount of organic crystal form control agent added is 0.02% to 1.00%, the amount of inorganic phosphate crystal form control agent added is 0.01% to 0.50%, and the amount of soluble magnesium salt added is 0.05% to 2.00% based on magnesium ions.
[0018] Preferably, the carbon dioxide-containing gas in step S5 is a mixture of carbon dioxide with a volume concentration of 10% to 100% and air, nitrogen and / or industrial gases containing carbon dioxide that have been dust-removed and cooled, and the gas flow rate per unit volume of carbonization precursor liquid is 0.05 to 1.50 L / (min·L).
[0019] Preferably, step S5 employs segmented carbonization: during the period from the start of the carbonization reaction until the cumulative amount of carbon dioxide introduced reaches 10% to 40% of the theoretical requirement, gas is introduced at a first gas flow rate; subsequently, gas is introduced at a second gas flow rate, wherein the first gas flow rate is 0.30 to 0.80 times the second gas flow rate.
[0020] Preferably, step S5 uses a stirred reactor with baffles, the linear velocity of the impeller tip is 1.5 to 6.0 m / s, or the stirring power per unit volume of carbonization precursor liquid is 0.2 to 3.0 kW / m³; the carbon dioxide-containing gas is introduced from below the impeller through an annular distributor, a porous distributor or a microporous aerator.
[0021] Preferably, step S5 uses a pH of 6.8 to 8.5 as the carbonization endpoint, and further uses a pH decrease of no more than 0.15 within 2 to 10 minutes and / or an increase in the volume concentration of carbon dioxide in the exhaust gas as auxiliary endpoint criteria; after reaching the carbonization endpoint, ventilation is stopped or switched to purging with a gas that does not contain carbon dioxide.
[0022] Preferably, the aging temperature in step S6 is the carbonization endpoint temperature to 60°C, the aging time is 15 to 240 minutes, and during the aging period, the stirring is carried out at a low speed or intermittently at 10% to 50% of the stirring speed during the carbonization stage.
[0023] Preferably, in step S6, the separated filter cake is subjected to two or more countercurrent washings using deionized water, softened water, or calcium carbonate saturated water until the conductivity of the final washing solution is not higher than 2.0 mS / cm, or the mass fraction of chloride ions in the dry basis product is not higher than 0.30%.
[0024] Preferably, the drying in step S6 is performed using at least one of vacuum drying, spray drying, flash drying, or fluidized bed drying at 60–120°C; the dispersion treatment is performed using mechanical depolymerization, air jet milling, needle milling, classification, or a combination thereof, so that the dispersed nano-calcium carbonate has a D50 of 20–100 nm and a D90 of no more than 200 nm.
[0025] Preferably, the ammonium chloride-containing mother liquor and at least part of the washing liquid obtained from solid-liquid separation in step S6 are desolvated and their concentrations adjusted before being returned to step S2, and ammonium chloride is added according to the measured content of ammonium chloride in the circulating liquid; the ammonia recovered in step S2 is returned to step S4 to form a closed-loop circulation of ammonia and ammonium chloride.
[0026] Preferably, the circulating mother liquor is bypassed for purification, with the bypass volume being 1% to 20% of the total circulating mother liquor. The bypass purification includes removing suspended solids, reducing the content of soluble miscellaneous salts, and adding at least one of the following: the amount of mother liquor returned and the amount of fresh ammonium chloride added are controlled based on the detection results of chloride ions, ammonium ions, calcium ions, and conductivity.
[0027] Preferably, the primary particles of the nano-calcium carbonate have a D50 of 20-100 nm, a D90 of no more than 200 nm, and a dry basis chloride ion mass fraction of no more than 0.30%.
[0028] The beneficial effects of this invention are: This invention uses calcium carbide sludge, an industrial solid waste, as a calcium source and carbon dioxide gas as a carbon source for carbonization. Through ammonium chloride conversion, impurity separation, calcium-containing solution purification, and controlled carbonization, the effective calcium components in calcium carbide sludge are converted into high-value-added nano-calcium carbonate. This realizes the transformation of industrial solid waste calcium carbide sludge from low-value-added disposal and utilization to high-value inorganic functional material utilization, which is conducive to improving the resource utilization level of calcium carbide sludge and reducing the dependence of nano-calcium carbonate production on traditional calcium resources such as high-purity limestone.
[0029] This invention combines the resource utilization of calcium carbide sludge with the mineralization and utilization of carbon dioxide. During the alkaline carbonation process, carbon dioxide enters the liquid phase and is converted into carbonate and / or bicarbonate ions, which further react with calcium components to form calcium carbonate. The carbon dioxide involved in the reaction is ultimately converted into stable carbonate components in nano-calcium carbonate. Therefore, this invention forms a resource conversion pathway of "industrial solid waste calcium carbide sludge—effective calcium resource extraction—carbon dioxide mineralization reaction—high-value nano-calcium carbonate product," achieving synergy between solid waste resource utilization, carbon dioxide resource utilization, and high-value calcium carbonate preparation. It has significant value in comprehensive resource utilization and carbon emission reduction applications.
[0030] This invention can use a mixture of carbon dioxide, air, and nitrogen within a certain concentration range, or industrial carbon dioxide-containing gas that has undergone dust removal, cooling, and necessary purification treatment as a carbonization gas source. This allows industrial carbon dioxide-containing gas to directly participate in the preparation of high-value-added nano-calcium carbonate, expanding the range of gas sources for carbon dioxide resource utilization and mineralization, and increasing the possibility of coupling this process with industrial carbon dioxide-containing gas sources.
[0031] This invention converts calcium hydroxide in carbide sludge into soluble calcium chloride via ammonium chloride conversion, and removes silicon, carbon slag, and other insoluble impurities through solid-liquid separation. Simultaneously, by adjusting the pH of the calcium-containing solution, incubating for precipitation, adsorption, and precision filtration, the interference of impurities such as iron, aluminum, magnesium, and suspended solids on calcium carbonate nucleation and crystal growth is further reduced. This significantly improves the purity of the carbonation precursor solution, creating favorable conditions for the preparation of nano-calcium carbonate with small particle size, narrow particle size distribution, and stable quality.
[0032] This invention measures the moisture content and effective calcium hydroxide content of calcium carbide sludge before conversion, and controls the amount of ammonium chloride added based on the effective calcium hydroxide content. This method can adapt to calcium carbide sludge raw materials from different sources, with different moisture contents and different effective calcium contents, reducing incomplete calcium conversion caused by insufficient ammonium chloride addition and raw material waste and increased mother liquor salt load caused by excessive addition, thereby improving raw material utilization and production process stability.
[0033] This invention utilizes a conversion reaction between ammonium chloride and calcium hydroxide to obtain a calcium-containing solution under relatively mild conditions. The ammonia produced in the reaction can be collected, defoamed, condensed, and absorbed through a closed or slightly negative pressure operation, and then returned to the carbonization system for reuse, thereby reducing ammonia escape and consumption of fresh ammonia feedstock. The ammonium chloride-containing mother liquor and at least a portion of the washing liquid obtained from solid-liquid separation can also be returned to the conversion step after solidification and concentration adjustment, forming a material cycle together with ammonia recovery. This helps reduce the consumption of fresh ammonium chloride and process water, as well as the discharge of saline wastewater.
[0034] This invention establishes an alkaline carbonation system by adjusting the calcium ion concentration in a calcium-containing solution and adding ammonia water and / or introducing ammonia gas. This promotes the rapid conversion of carbon dioxide in the liquid phase, increasing the supersaturation and nucleation rate of calcium carbonate. By further controlling the carbonation temperature, carbon dioxide volume concentration, gas flow rate per unit volume of precursor liquid, stirring intensity, and carbonation endpoint, and by using a crystal form control agent to regulate crystal growth, it promotes concentrated and uniform nucleation of calcium carbonate, inhibits excessive crystal growth and particle agglomeration, thereby obtaining nano-calcium carbonate with small primary particle size, narrow particle size distribution, and good dispersion performance.
[0035] This invention employs segmented carbonization and enhanced gas-liquid dispersion, which can improve the mass transfer and reaction efficiency of carbon dioxide in the carbonization precursor liquid, and reduce non-uniform nucleation, local over-carbonization, and crystal form loss caused by excessively high local carbon dioxide concentration. By judging the carbonization endpoint through pH stability and / or changes in tail gas carbon dioxide concentration, it can reduce the free calcium residue caused by insufficient carbonization and the calcium carbonate dissolution, crystal form transformation, and particle coarsening caused by excessive carbonization, thereby improving carbon dioxide utilization efficiency and product batch stability.
[0036] This invention further reduces the residues of ammonium chloride, calcium chloride, and other soluble salts in nano-calcium carbonate through controlled aging, multi-stage countercurrent washing, solid-liquid separation, drying, and dispersion treatment, thereby improving product purity, particle size stability, and application performance. This enables the deep and high-value utilization of calcium resources in carbide sludge from industrial solid waste to high-value-added nano-calcium carbonate products. Attached Figure Description
[0037] The above-described aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which: Figure 1 This is a schematic diagram of a method for preparing nano-calcium carbonate using carbide sludge, ammonium chloride, and carbon dioxide according to an embodiment of the present invention. Detailed Implementation
[0038] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] A method for preparing nano-calcium carbonate using calcium carbide sludge, ammonium chloride, and carbon dioxide is disclosed. The calcium carbide sludge can be a wet-discharged slurry, a filter cake formed by pressure filtration, or a powder formed by low-temperature drying. Preferably, the dry basis Ca(OH)₂ content of the raw material is not less than 60%, but if the content is low, it can still be achieved by increasing the solid-liquid separation intensity and adding ammonium chloride according to the effective calcium content. The raw material may contain CaCO₃, SiO₂, unreacted carbonaceous matter, iron and aluminum oxides, and a small amount of magnesium compounds; the original CaCO₃ and silicates are mainly separated as insoluble substances after leaching. Fresh industrial ammonium chloride can be used, or a recycled ammonium chloride solution obtained by solidification and concentration adjustment of carbonation mother liquor. The carbon dioxide can be bottled or liquid-gasified CO₂, or CO₂-containing gas after dust removal, oil removal, cooling, and removal of obvious acidic impurities.
[0040] Applicable equipment should include at least the following: leaching reactors with heating / cooling jackets, stirrers, and gas phase outlets; demisters, condensers, and ammonia absorbers; coarse filters or filter presses, and precision filters; carbonization reactors with baffles, thermometers, pH electrodes, gas distributors, and exhaust ports; aging tanks, solid-liquid separation equipment, washing devices, dryers, and depolymerization equipment. All equipment and pipelines in contact with ammonia should be kept sealed, and the gas phase system should be maintained at a slight negative pressure of -50 to -500 Pa. pH electrodes should be of a high ionic strength resistant type and should be calibrated at two points using pH 7.00 and pH 10 buffer solutions before the start of each batch.
[0041] The wet calcium carbide sludge is first passed through a 10-30mm screen to remove metal, coke lumps, and large particles, then slurryed at a dry solids to water ratio of 1:(1-5). It is dispersed for 10-60 minutes using a high-speed disperser or paddle mixer to dissociate the agglomerated calcium carbide sludge; if necessary, it is passed through a 0.5-2.0mm sieve. The dried calcium carbide sludge should be added to the water slowly, with local ventilation activated during the feeding process to prevent dust generation and localized overheating. The pretreated slurry should ideally be introduced into the leaching process within 2 hours; if temporary storage is necessary, low-speed stirring should be maintained to prevent sedimentation and stratification.
[0042] When calcium carbide sludge contains significant coarse sand, hydrocyclone or sedimentation can be used to remove the sand before adding ammonium chloride. When there are many fine particles in the calcium carbide sludge, excessively fine pre-filtration should be avoided to prevent loss of effective Ca(OH)2. The criteria for pretreatment are that there are no visible lumps in the slurry, and the residue on the specified sieve after sampling changes by no more than 5% between two consecutive tests.
[0043] An 8%–30% (w / w) ammonium chloride solution is added to the leaching reactor. Stirring is started and the temperature is raised to 25–80°C. Then, the calcium carbide slurry is added continuously or in batches. To avoid sudden large-scale ammonia release and foam entrainment, the calcium carbide slurry addition is preferably completed within 30–90 minutes, and the temperature fluctuation of the reaction solution should not exceed ±3°C. Based on available Ca(OH)₂, the NH₄Cl / Ca(OH)₂ molar ratio can be 1.80–2.40, preferably 1.95–2.20. When the molar ratio is less than 2, a small amount of unreacted alkali can be retained to assist in impurity precipitation, but this will reduce the calcium extraction rate. When the molar ratio is significantly greater than 2, it will increase the salt load of the mother liquor; therefore, it should be determined in conjunction with the recovery rate.
[0044] After adding the calcium carbide sludge, maintain the temperature at 40–70℃ for 30–180 minutes. The stirring intensity should be such that the solid does not form a stable sediment at the bottom of the vessel. In laboratory reactors, a stirring speed of 300–800 r / min can be used; for scale-up operations, the paddle tip linear velocity should be controlled at 1.5–4.5 m / s. Take samples every 15–30 minutes, filter, and measure the calcium ion concentration in the filtrate, as well as the residual reactive calcium in the filter residue. The leaching is considered complete when the increase in calcium ion concentration between two consecutive leaching cycles does not exceed 2%, or when the reactive Ca(OH)₂ in the filter residue decreases to a preset value.
[0045] Part of the generated ammonia dissolves in the liquid phase, while the rest enters the gas phase. The gas phase first passes through a wire mesh demister to remove entrained droplets, then through a condenser at 15–30°C to recover water and ammonium chloride mist droplets, before being sent to a two-stage absorber. The first stage uses a purified calcium-containing solution for absorption, making it a direct precursor liquid for ammonia-containing carbonization; the second stage uses water or a 1%–5% (w / w) dilute ammonia solution for absorption. The absorber temperature is preferably 5–25°C, and the tail gas is discharged after treatment to meet standards. The resulting ammonia solution should be determined by acid titration to determine the free ammonia concentration, and then returned to the carbonization process according to the free ammonia / calcium ion molar ratio.
[0046] After leaching, plate and frame filtration or centrifugation can be performed directly at 40–65℃. The coarse filtration accuracy can be 20–100 μm. The filter cake is washed with water equivalent to 0.3–1.5 times its wet weight in one to three stages, and the washing liquid is added to the main filtrate. For feed solutions containing a large amount of fine suspended solids, a small amount of filter residue from the previous purification batch can be added as a filter aid layer, or inert filter aids such as diatomaceous earth can be used. However, the filter aids must not introduce soluble impurities that affect carbonization into the calcium-containing solution.
[0047] The calcium-containing filtrate is purified before carbonization. The pH can be slowly adjusted to 8.0–10.5 using recovered ammonia water, and then kept at 30–60℃ for 10–60 minutes to allow impurities such as iron and aluminum to precipitate as hydroxides, and to adsorb residual colloids. During pH adjustment, prolonged aeration in an open container should be avoided to prevent the absorption of CO2 from the air and premature precipitation of CaCO3. After holding at this temperature, the filtrate is first filtered through a 1–20 μm precision filter, and then, if necessary, through a 0.1–5 μm security filter. If the raw material contains a small amount of oil or colored organic matter, 0.01%–0.20% (by weight of the solution) of powdered activated carbon can be added before fine filtration, stirred for 10–30 minutes, and then filtered.
[0048] After purification, calcium ions, iron, aluminum, magnesium, suspended solids, and conductivity are determined. Calcium ions can be determined by EDTA complexometric titration or a calibrated inductively coupled plasma method. The calcium ion concentration is adjusted to 0.20–1.50 mol / L, preferably 0.30–1.00 mol / L, by adding deionized water, evaporation and concentration, or mixing different batches of solution. The calcium-containing solution before carbonization should be clear or only slightly opalescent, and there should be no visible sediment.
[0049] A measured amount of purified calcium-containing solution is added to the carbonization reactor and the temperature is lowered to the target carbonization temperature. The molar ratio of free ammonia to calcium ions is adjusted to 1.80–2.40, preferably 1.95–2.20, by adding recovered ammonia, supplementing ammonia, or introducing metered ammonia gas, and the initial pH is adjusted to 10.5–12.5. When using ammonia gas, it should be introduced below the liquid surface while simultaneously activating cooling to suppress ammonia escape; when using ammonia solution, it should be added in batches, and the mixture should be stirred for at least 5 minutes after each addition before measuring the pH.
[0050] The crystal form control agent can be added all at once before CO2 is introduced, or 30%–70% of the total amount can be added before aeration, with the remainder added when the accumulated CO2 reaches 10%–40% of the theoretical requirement. Water-soluble crystal form control agents should be pre-prepared as a 1%–20% solution and filtered through a 5μm filter. For citrate, polyacrylate, or polyethylene glycol, 0.02%–1.00% can be added based on the theoretical CaCO3 mass; for hexametaphosphate or pyrophosphate, 0.01%–0.50% can be added; for soluble magnesium salts such as MgCl2, 0.05%–2.00% can be added based on the Mg²⁺ content of the theoretical CaCO3 mass. When multiple control agents are combined, the total amount should be determined through small-scale testing to avoid excessive adsorption that inhibits carbonization or increases the washing load.
[0051] The carbonization reactor is preferably equipped with 2 to 4 vertical baffles, and the agitator is a turbine type, propeller type, or a combination thereof; the gas distributor is located 0.1 to 1.0 times the impeller diameter below the lower impeller. For laboratory reactors, a speed of 300 to 1200 r / min can be used; for engineering scale-up, a blade tip linear velocity of 1.5 to 6.0 m / s or a power per unit volume of 0.2 to 3.0 kW / m³ is used as a similarity criterion. The CO2 volume fraction can be 10% to 100%, and the inlet mixed gas flow rate per unit volume of precursor liquid is 0.05 to 1.50 L / (min·L). The jacket cooling capacity should be sufficient to maintain the temperature within ±2℃ of the set value during carbonization.
[0052] To achieve a high and uniform nucleation rate, segmented aeration is preferred. During the initial aeration period until the accumulated CO2 reaches 10%–40% of the theoretical amount, a lower initial flow rate is used to allow for rapid CO2 absorption in the strongly alkaline system and to avoid localized low pH near the gas distributor. After nucleation, the flow rate is switched to a second flow rate, with the initial flow rate being 0.30–0.80 times the second flow rate. Alternatively, the total gas volume can be kept constant while gradually increasing the inlet CO2 concentration. Throughout the process, temperature, pH, gas volume, and inlet and tail gas CO2 concentrations are recorded at least once every 1–5 minutes.
[0053] The carbonation reaction proceeds according to the sequence CaCl2 + 2NH3 + CO2 + H2O → CaCO3↓ + 2NH4Cl. As the reaction progresses, the pH gradually decreases from 10.5 to 12.5. When the pH reaches 6.8 to 8.5, continue aeration for 2 to 10 minutes. If the pH decrease is no greater than 0.15 and the CO2 concentration in the tail gas increases significantly compared to the previous stage, the calcium ion conversion can be considered nearing completion. Immediately after reaching the endpoint, stop CO2 aeration, or introduce air / nitrogen for 1 to 5 minutes to replace the high concentration of CO2 in the reactor, preventing further acidification that could lead to calcium carbonate dissolution and a wider particle size distribution.
[0054] If the pH drops by more than 0.5 within 1 minute during the initial stage of carbonization, it indicates that the CO2 mass transfer is too fast relative to the mixing. The gas flow rate should be reduced by 20% to 50%, the stirring intensity should be increased, or the inlet CO2 concentration should be reduced. If the temperature exceeds the set value by 3°C during the middle and later stages of carbonization, the aeration should be stopped or reduced and the cooling water flow rate should be increased. If large flocs appear in the slurry, the remaining crystal form control agent can be added in the form of a dilute solution and the mixing time should be extended. However, strong acids should not be used to directly adjust the carbonization endpoint.
[0055] After carbonization, the slurry is aged at the endpoint temperature of 60°C for 15–240 min. To maintain a small particle size, aging at 10–35°C for 30–120 min with low-speed stirring at 10%–50% of the carbonization stirring speed is preferred. To improve crystal integrity, the temperature can be increased to 40–60°C after carbonization at a rate of 0.2–1.0°C / min before further aging. During aging, CO2 is not introduced, and the container is kept sealed or protected with a low-flow-rate nitrogen atmosphere.
[0056] The aged slurry can be separated using a centrifuge, vacuum filter, or filter press. The filter cake is washed at least twice countercurrently with deionized water, softened water, or CaCO3-saturated water. The volume of water used in each stage of washing can be 0.5 to 3.0 times the dry weight of CaCO3. The washing endpoint is determined by the conductivity of the final wash solution not exceeding 2.0 mS / cm or the chloride ion content of the finished product not exceeding 0.30% on a dry weight basis. To avoid hard agglomeration caused by prolonged static storage of the filter cake, it should be put into a re-slurrying or drying step within 4 hours after the final washing.
[0057] The wet filter cake can be mixed with water to form a slurry with a mass fraction of 10%–35% and then spray-dried; alternatively, it can be dried under vacuum, flash, or fluidized bed at 60–120°C until the moisture content is no higher than 1.0%. After drying, it is depolymerized using an air jet mill, needle mill, or high-speed mechanical mill, and, if necessary, classified. The depolymerization equipment should be designed to destroy soft aggregates without significantly damaging primary particles. For products requiring surface modification, fatty acid salts or coupling agents can be added after washing and before drying, but this treatment is not a necessary step in the basic preparation route of this invention.
[0058] The main soluble component of the carbonization mother liquor is NH4Cl. The mother liquor obtained from solid-liquid separation is combined with the high-concentration washing liquid from the pre-washing stage. After removing entrained CaCO3 through 1–20 μm filtration, NH4⁺, Cl⁻, Ca²⁺, and conductivity are measured. The required NH4Cl is calculated based on the amount of effective Ca(OH)₂ added in the next batch. The circulating liquid is adjusted to 8%–30% by adding water, evaporation, or adding solid / concentrated ammonium chloride solution before being returned to the leaching reactor. The actual NH4Cl content in the circulating liquid is calculated based on the lower equivalence between Cl⁻ and NH4⁺ to avoid miscounting other chloride salts as effective NH4Cl.
[0059] To suppress the accumulation of soluble impurities, 1%–20% of the circulating mother liquor can be treated as bypass liquid. The bypass liquid can be concentrated and crystallized to separate impurities, or partially removed by ion exchange or membrane methods. Alternatively, after compensating for material balance, it can be sent to a compliant wastewater treatment unit. Condensate and low-conductivity wash water from the final stage should be used preferentially for system makeup water. Ammonia generated during leaching is recovered as described above and returned to the carbonization precursor liquor, thus allowing NH4Cl to release ammonia during leaching and regenerate during carbonization, reducing the consumption of fresh ammonia water and ammonium chloride.
[0060] For calcium ion concentration determination using EDTA complexometric titration, an appropriately diluted sample can be used, and the endpoint determined using a calcium indicator at approximately pH 12. For samples with high magnesium content, selective masking or instrumental methods should be employed for verification. Free ammonia is determined by standard acid titration, with carbonate alkalinity subtracted. Chloride ions can be determined by silver nitrate titration or ion chromatography. Before particle size analysis, the sample is dispersed at 1 g / L in water or a medium compatible with the product surface, a fixed amount of dispersant is added, and the mixture is sonicated at a fixed power for 5–10 min; the same dispersion conditions must be used for the same set of comparative data. Example 1:
[0061] 10.00 kg of wet calcium carbide sludge was taken, and its moisture content was measured to be 35.0%, with a dry basis Ca(OH)₂ mass fraction of 78.0%. Based on this, the effective Ca(OH)₂ was calculated to be 5.070 kg, or 68.43 mol. According to the NH₄Cl / Ca(OH)₂ molar ratio of 2.05, the required amount of pure NH₄Cl was 7.50 kg. 7.50 kg of NH₄Cl was prepared into a 20.0% mass fraction solution and added to a 60 L jacketed sealed leaching vessel. The temperature was raised to 55 °C. Within 60 min, pre-dispersed calcium carbide sludge slurry that had passed through a 1 mm sieve was added, maintaining a temperature of 55 ± 2 °C and stirring at 450 r / min. After the addition was complete, the reaction continued for another 90 min. The ammonia-containing tail gas was defoamed, condensed at 20 °C, and then absorbed by water in a two-stage process.
[0062] The reaction solution was filtered hot using a plate and frame filter press. The filter cake was washed twice with 8.0 kg of water, and the washings were combined with the filtrate. The pH of the combined filtrate was adjusted to 9.2 with recovered ammonia water, and the solution was kept at 50℃ for 30 min. The solution was then filtered through 10 μm and 1 μm filters. After determining the Ca²⁺ concentration, a purified solution equivalent to 12.00 mol Ca²⁺ was taken and diluted with water to a final volume of 20.0 L, resulting in a Ca²⁺ concentration of 0.600 mol / L. Titrated and standardized recovered ammonia water was added at a free ammonia / Ca²⁺ molar ratio of 2.05, and the initial pH was adjusted to 11.6.
[0063] The theoretical mass of CaCO3 is 1.201 kg. 1.80 g of sodium citrate was prepared into a 10% solution and added, then the mixture was cooled to 18°C. A six-bladed turbine with a diameter of 120 mm was used for stirring at 650 r / min; a CO2 / air mixture with a CO2 volume fraction of 30% was introduced through an annular distributor under the turbine. The flow rate was 6.0 L / min for the first 20 min, then increased to 12.0 L / min; the jacket temperature was maintained at 18 ± 2°C. After the pH dropped to 7.4, aeration continued for 3 min. Once the pH change was confirmed to be no more than 0.10, CO2 was stopped, and air was introduced for 2 min.
[0064] The slurry was aged at 20℃ and 150 r / min for 60 min, filtered, and then washed with deionized water in a three-stage countercurrent process until the conductivity of the final wash was below 1.5 mS / cm. The filter cake was vacuum dried at 90℃ for 8 h, and then depolymerized by airflow. Following the aforementioned unified dispersion and detection method, this embodiment was used to obtain dispersed nano-calcium carbonate with a D50 of 40–90 nm and a D90 of no more than 180 nm. Example 2:
[0065] Filter carbide sludge with a dry basis Ca(OH)₂ content of 82.5% was used. It was impregnated at 60℃ for 120 min with an 18% ammonium chloride solution at a dry weight ratio of NH₄Cl / Ca(OH)₂ of 2.10. After coarse filtration, the pH of the filtrate was adjusted to 9.5, kept at this temperature for 20 min, and then subjected to a 5μm fine filtration. The purified solution was used to prepare a 10.0 L carbonization solution with a Ca²⁺ concentration of 0.900 mol / L, containing 9.00 mol of Ca²⁺. The free ammonia / Ca²⁺ molar ratio was adjusted to 2.10 and the initial pH to 11.8 using 25% ammonia water.
[0066] The theoretical mass of CaCO3 is 0.901 kg. Weigh 0.72 g of sodium polyacrylate and prepare a 2% solution; add 0.43 g before aeration, and add the remaining 0.29 g when the cumulative CO2 aeration reaches 25% of the theoretical amount. Cool the precursor solution to 10°C, stir at 900 rpm, and aeration rate of 99.5% CO2 is introduced: 1.5 L / min for the first 10 min, and 3.0 L / min thereafter. The endpoint is defined as pH 7.6, maintained at a change of no more than 0.15 within 5 min.
[0067] After carbonization, the product was aged at 15°C for 45 minutes, centrifuged, and then subjected to three stages of washing with water at 2.0, 1.5, and 1.0 times the dry basis product weight. It was then vacuum dried at 80°C and mechanically depolymerized. This embodiment utilizes a combination of high Ca²⁺ concentration, low temperature, and staged addition of polymer control agents to suppress secondary agglomeration while increasing unit equipment capacity. If the viscosity increases significantly in the initial stage of carbonization, the total amount of sodium polyacrylate should be reduced by 20%, and a small-scale test should be conducted again. Example 3:
[0068] 50.0 L of purified calcium-containing solution with a Ca²⁺ concentration of 0.450 mol / L was prepared according to the leaching and purification method of Example 1, containing 22.50 mol of Ca²⁺. Recovered ammonia water was added to achieve a free ammonia / Ca²⁺ molar ratio of 2.08 and an initial pH of 11.5. Based on a theoretical CaCO₃ mass of 2.252 kg, 2.25 g of sodium citrate and 10.0 g of MgCl₂·6H₂O were added; both were prepared as 10% solutions and then added.
[0069] The feed solution was maintained at 25±2℃, and agitated at 520 r / min using a 180 mm diameter lower propeller and a 160 mm diameter upper turbine propeller. Simulated industrial carbon-containing gas, after dust removal, oil removal, and cooling to 25℃, was introduced, with a CO2 volume fraction of 15%, the remainder being nitrogen and air. The gas flow rate was 10 L / min for the first 30 minutes, and then 20 L / min thereafter. Inlet and exhaust CO2 levels were recorded online, and aeration was stopped when the pH reached 7.8 and the exhaust CO2 volume fraction continued to rise.
[0070] After aging at 30°C for 90 minutes, the slurry was filtered and washed, redispersed to a solid content of 20%, and dried using a spray drying method with an inlet temperature of 170°C and an outlet temperature of 85°C, followed by depolymerization using a low-energy gas flow. This example illustrates that a low-concentration CO2 gas source can be used, but the lower CO2 partial pressure must be compensated for by increasing the gas-liquid contact time, controlling the exhaust gas, and avoiding excessive gas flow. Example 4:
[0071] The purified calcium-containing solution was prepared into a 30.0 L solution with a Ca²⁺ concentration of 0.400 mol / L, and cooled to 8 °C. Under stirring at 600 rpm and jacket cooling, ammonia-containing gas recovered from the leaching process and defoamed was slowly introduced below the liquid surface; free ammonia was titrated every 5 min. Ammonia gas was introduced when the free ammonia / Ca²⁺ molar ratio reached 2.00 and the pH reached 11.7, and stirring was continued for 10 min. 0.10% polyethylene glycol and 0.05% sodium hexametaphosphate were added according to the theoretical CaCO₃ mass.
[0072] A mixed gas with a CO2 volume fraction of 50% was introduced at 12℃. The gas flow rate was 4.0 L / min until the cumulative CO2 reached 30% of the theoretical amount, and then 8.0 L / min. The impeller tip velocity was maintained at 3.5 m / s, and gas introduction was stopped after the pH reached 7.3. The slurry was aged at 20℃ for 60 min and then filtered, subjected to three-stage washing, spray drying, and depolymerization. This method reduces the step of separately preparing concentrated ammonia water; to prevent ammonia escape, the tail gas from the ammonia absorption stage should be returned to the second-stage water absorber and should not be directly discharged. Example 5:
[0073] Collect the carbonization filtration mother liquor and the first-stage washing liquid from Example 1, and measure NH4⁺, Cl⁻, Ca²⁺, and conductivity after filtration through a 5μm filter. Calculate the effective NH4Cl based on the lower equivalence of NH4⁺ and Cl⁻, and adjust the circulating liquid to a mass fraction of 20.0% by evaporation or water replenishment. Based on the effective Ca(OH)₂ content of the next batch of calcium carbide sludge, calculate the total demand using an NH4Cl / Ca(OH)₂ molar ratio of 2.05, and account for the shortfall that cannot be met by simply replenishing the circulating liquid.
[0074] The second and third batches were operated under the leaching conditions of 55°C and 90 min as described in Example 1. After each batch of carbonization was completed, 5% of the total mother liquor of that batch was used as bypass liquid, and the remainder was reused; the water and NH4Cl lost in the bypass were replenished with condensate and fresh NH4Cl, respectively. The concentrations of Cl⁻, NH4⁺, Ca²⁺, iron, magnesium, and conductivity were recorded before and after each batch of leaching; when any impurity increased by more than 20% compared to the previous batch or when colloids affecting fine filtration appeared, the bypass ratio was increased to 10%–20%.
[0075] The ammonia produced during leaching undergoes two-stage absorption and is returned to each batch of carbonization steps based on the titration results, maintaining the free ammonia / Ca²⁺ molar ratio at 2.05. The core control of this circulation method lies in separately balancing the available NH₄Cl, recovered ammonia, and accumulated impurities, rather than simply refluxing at a fixed volume. This method allows for continuous operation without altering the nucleation and carbonization control conditions. Example 6:
[0076] A metered 20% ammonium chloride circulating solution was added to an 800L leaching vessel. Based on a batch of 100kg wet calcium carbide sludge with a moisture content of 40.0% and a dry basis Ca(OH)₂ content of 75.0%, the available Ca(OH)₂ is 45.0kg, or 0.607kmol; 66.6kg of pure NH₄Cl is required at a molar ratio of 2.05. Any shortfall in the circulating solution was made up with fresh NH₄Cl. The calcium carbide sludge, after being prepared into a slurry with approximately 25% solids content, was added within 90 minutes, and the reaction was carried out at 55℃ and a paddle tip linear velocity of 2.5m / s for 120 minutes. After pressure filtration, washing, and fine filtration, a purified calcium-containing solution was obtained.
[0077] 500L of purified calcium-containing solution with a Ca²⁺ concentration of 0.500mol / L was added to a 650L carbonization reactor, containing a total of 0.250kmol of Ca²⁺, corresponding to 25.0kg of theoretical CaCO₃. The free ammonia / Ca²⁺ molar ratio was adjusted to 2.05 using recovered ammonia and replenishing ammonia water, and sodium citrate (0.12% of the theoretical CaCO₃ mass) was added. The carbonization reactor employed a four-baffle, double-layer impeller, and annular gas distributor with an impeller tip linear velocity of 3.2m / s, and the jacket maintained the temperature at 20±2℃.
[0078] A mixed gas with a CO2 volume fraction of 30% was introduced at a flow rate of 100 L / min for the first 30 minutes, followed by 200 L / min. A closed-loop correction of ±20% was applied to the flow rate based on the pH decrease slope and the CO2 concentration in the exhaust gas. After the pH reached 7.5 and stabilized for 5 minutes, the gas flow was stopped, and the mixture was aged at a low speed of 20°C for 90 minutes. Following filtration, a three-stage countercurrent washing process was employed, followed by spray drying and gas-air depolymerization. During scale-up, the laboratory rotation speed was not directly replicated; instead, the paddle tip linear velocity, gas flow rate per unit volume, gas distribution area, and cooling capacity were kept similar to ensure reproducible mixing and mass transfer conditions.
[0079] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing nano-calcium carbonate using calcium carbide sludge, ammonium chloride, and carbon dioxide, characterized in that, Includes the following steps: S1. The moisture content and calcium hydroxide content of the calcium carbide mud are determined. The calcium carbide mud is measured on a dry basis. The calcium carbide mud is mixed with water and then crushed, sieved or wet dispersed to obtain calcium carbide mud slurry. S2. The calcium carbide slurry is mixed with ammonium chloride solution, and a conversion reaction is carried out under the conditions that the molar ratio of ammonium chloride to effective calcium hydroxide in calcium carbide slurry is 1.80 to 2.40 and the reaction temperature is 25 to 80°C, so that calcium hydroxide is converted into soluble calcium chloride and ammonia is generated. Then, solid-liquid separation is carried out to remove insoluble impurities and obtain a calcium-containing solution containing calcium chloride. S3. The calcium-containing solution is purified, and the calcium ion concentration of the purified calcium-containing solution is adjusted to 0.20-1.50 mol / L; S4. Add ammonia water and / or introduce ammonia gas into the adjusted calcium-containing solution to make the system alkaline, and add a crystal form control agent to obtain the carbonization precursor solution. S5. Under the conditions of 5-45℃ and stirring, a gas containing carbon dioxide is introduced into the carbonation precursor liquid. By controlling the carbon dioxide volume concentration, the gas flow rate per unit volume of precursor liquid, the stirring intensity and the carbonation endpoint, calcium ions react with carbon dioxide to form calcium carbonate crystal nuclei and inhibit the continued growth of crystal grains, thus obtaining nano-calcium carbonate slurry. S6. The nano-calcium carbonate slurry is subjected to aging, solid-liquid separation, washing, drying and dispersion treatment in sequence to obtain nano-calcium carbonate.
2. The method according to claim 1, characterized in that, The calcium carbide sludge mentioned in step S1 is at least one of wet-discharged calcium carbide sludge, filter-pressed calcium carbide sludge, or dried calcium carbide sludge; the calcium carbide sludge has a calcium hydroxide mass fraction of 45% to 95% on a dry basis, and particles and foreign matter with a particle size greater than 1 mm are separated from the calcium carbide sludge slurry before the conversion reaction.
3. The method according to claim 1, characterized in that, In step S2, the mass fraction of the ammonium chloride solution is 8%–30%, the molar ratio of ammonium chloride to effective calcium hydroxide is 1.95–2.20, and the temperature of the conversion reaction is 40–70°C and the time is 30–180 min.
4. The method according to claim 1, characterized in that, Step S2 is carried out using a closed or slightly negative pressure reactor. The ammonia-containing gas discharged from the reactor is successively defoamed and condensed, and then absorbed by water, dilute ammonia water, or purified calcium-containing solution. The resulting ammonia water or ammonia-containing calcium-containing solution is returned to step S4.
5. The method according to claim 1, characterized in that, The solid-liquid separation in step S2 includes sedimentation, centrifugation, plate and frame filtration, membrane filtration or a combination thereof; the filtration accuracy of the solid-liquid separation is 0.5 to 100 μm, and the resulting filter residue is washed with water, and the washing liquid is incorporated into the calcium-containing solution.
6. The method according to claim 1, characterized in that, The purification step S3 includes: adjusting the pH of the calcium-containing solution to 8.0–10.5 and keeping it at a temperature of 10–60 min, so that at least one of the impurities, such as iron, aluminum, and magnesium, forms a precipitate or is adsorbed by insoluble particles; and then removing the impurities by at least one of a 1–20 μm precision filter and a 0.1–5 μm security filter.
7. The method according to claim 1, characterized in that, In step S3, the suspended solids content in the purified calcium-containing solution is no higher than 200 mg / L, and the calcium ion concentration is adjusted to 0.30–1.00 mol / L by diluting with water, evaporating and concentrating, or mixing with calcium-containing solutions of different concentrations.
8. The method according to claim 1, characterized in that, In step S4, the amount of ammonia water and / or ammonia gas added is calculated as free ammonia, the molar ratio of free ammonia to calcium ions is 1.80 to 2.40, and the initial pH of the carbonization precursor solution is adjusted to 10.5 to 12.
5.
9. The method according to claim 1, characterized in that, The crystal form control agent is selected from one or more of citric acid, citrate, polyacrylic acid or its salts, hexametaphosphate, pyrophosphate, ethylenediaminetetraacetic acid or its salts, polyethylene glycol, sucrose, and soluble magnesium salts; based on the theoretical mass of calcium carbonate produced, the amount of organic crystal form control agent added is 0.02% to 1.00%, the amount of inorganic phosphate crystal form control agent added is 0.01% to 0.50%, and the amount of soluble magnesium salt added is 0.05% to 2.00% based on magnesium ions.
10. The method according to claim 1, characterized in that, In step S5, the carbon dioxide-containing gas is a mixture of carbon dioxide with a volume concentration of 10% to 100% and air, nitrogen, and / or industrial gases containing carbon dioxide that have been dust-removed and cooled. The gas flow rate per unit volume of carbonization precursor liquid is 0.05 to 1.50 L / (min·L).